Effect of minimal shoes and slope on vertical and leg stiffness during running - Thibault Lussiana; Kim Hébert-Losier; Laurent Mourot (Elsevier, 2015)
Purpose: This study was designed to characterize and compare the vertical (kvert) and leg (kleg) stiffness measured during running in two different footwear conditions on negative, level, and positive slopes, using kinematic data only. Methods: Fourteen male recreational runners (age 23.4 ± 4.4 years, height 177.5 ± 5.2 cm, and body mass 69.5 ± 5.3 kg) were tested on 2 separate days within 1 week. At each session, subjects ran seven 5-min trials on a treadmill at 10 km/h, interspersed with 5 min of sitting passive recovery. Each trial was performed on a different slope gradient, ranging from −8% (downhill) to +8% (uphill), assigned in a random order. Furthermore, each subject ran one 5-min trial wearing minimal shoes (MS) and the subsequent trial wearing traditional shoes (TS) in a counter-balanced randomized order ensuring that each slope was ran once in MS and once in TS. Kinematic data were collected using a photocell measuring system and high-speed video camera, with kvert and kleg stiffness being calculated from these data. Results: Leg compression, contact times, and vertical displacement of the center of mass during running were significantly smaller in MS compared to TS across all slopes. In the two footwear conditions, step frequency significantly increased with a (positive) increase in slope. Kinematic analyses indicated that kleg was greater when running in MS than TS and this between-footwear difference remained similar across slopes. On the contrary, kvert did not change on the basis of footwear, but increased with positive increases in slope. Conclusion: This study showed that kvert and kleg during running respond differently to change in footwear and/or slope. These two stiffness measures can hence provide a unique insight on the biomechanical adaptations of running under varying conditions and their respective quantification may assist in furthering our understanding of training, performance, and/or injury in this sport.